Mosque Leadership in Muslim Minorities - Articulating a Dynamic Mission: a Theoretical Discussion - MIM. Jazeel; Zulkiple Abd Ghani (Universiti Sains Islam Malaysia, 2024)
Muslims living in non-Islamic lands,face numerous challenges. In that, they are likely to be subjected to persecution and they would, therefore, suffer from lack of means to assert their existence and multi-facet development. In this circumstance, Muslims 'needs and their expectations are to be met through Islamic systems and intuitions. With these arguments in view, the mosque as a prime intuition of Islam, can play the leadership role in accomplish growth and development in all aspects of Muslim life. The first and ultimate duty for a mosque leadership is to articulate its mission, which implies reasons,for its existence and responsibilities towards the stakeholders (jama'at). The central objective of the study is to provide in depth theoretical discussion on the mission of mosques. For this purpose, the Islamic textual sources, prophetic model and historical accounts were interpreted in order to conceptualize the mosque in Islam. It is followed by a serious criticism made on the opinion about the mosque as merely a house of worship. The Islamic concept of mosque derived from the discussion advocates a compelling mission ,for the mosque in order to lead the community for a holistic development of its jama'at considering of their context they are living as minorities. Ideally, this mission helps set strategic planning of the mosque and guides its actions and functions.